AGAMA DAN KEPERCAYAAN MASYARAKAT MELAYU SUNGAI JAMBU KAYONG UTARA TERHADAP BULAN SAFAR - Wahab Wahab; Hariansyah Hariansyah; Dewi Nurhayati, (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
Safar is one month in the Hijriyah Calendar. The Arabs since the time of Jahiliyah consider the safar month to be an unlucky month. This is still followed by some parts of the Melayu Sungai Jambu community. The community carries out the tradition of safar bathing and other rituals to obtain safety and avoiding bad luck on the safar month. Qualitative research using ethnographic methods determines the subject of religious leaders and traditional leaders, the techniques used to obtain information or data are non-participant observation, telephone interviews, and direct interviews. The results of this study that for the Melayu Sungai Jambu community to read congratulations and refuse prayers is a form of confidence to be saved from disaster and illness in the month of safar. Then read surah al-Fatihah, al-Ikhlas, an-Naas and al-Falak get a reward from Allah SWT. Furthermore, the safar bath is also a purified part of the reinforcements and diseases, besides that, it also removes odors, dust, and moisturizes the skin. However, the belief of the Sungai Jambu Malay community towards the safari month that brought disaster and disease contradicts the theory of Educational Theology and authentic Hadith about the safar month.